Monoclonal antibodies in inflammatory disease of the muscle and peripheral nervous system - J.J. Poza Aldea (Neurología (English Edition), 2012)
Introduction: A significant group of neuromuscular diseases are of autoimmune origin, but the classic immunomodulatory drugs are not often effective. For this reason, there is a need to find new more effective treatments that will lead to better control of these conditions, particularly those that are usually more resistant. In the last few years, the use of monoclonal antibodies against specific antigens of lymphocyte populations or against pro-inflammatory molecules has seen a great expansion, and has been demonstrated to be a useful alternative in autoimmune diseases.An intensive search was made in Medline using the key words: neuromuscular, myopathy, neuropathy, myasthenia, Lambert-Eaton, monoclonal antibody, rituximab, alemtuzumab, and anti-TNF-α. Development: Clinical trials performed to evaluate the efficacy of monoclonal antibodies in neuromuscular disease are very limited and of reduced size. Thus, the experience in this field is basically limited to anecdotal cases or short series of patients on open-label treatment. The published data are encouraging, with favourable responses having been observed in patients resistant to classic treatments and in diseases that do not normally respond to the usual immunosuppressant drugs. On the other hand, it has been observed that anti-TNF-α antibodies may trigger the appearance of autoimmune neuromuscular diseases. Conclusions: Monoclonal antibodies could be an effective alternative treatment in autoimmune neuromuscular diseases, but the favourable responses observed need to be confirmed by means of controlled clinical trials with a sufficient number of patients. Resumen: Introducción: Un importante grupo de enfermedades neuromusculares son de origen autoinmune, pero con relativa frecuencia los fármacos inmunomoduladores clásicos no son eficaces. Por este motivo, se hace necesario encontrar nuevos tratamientos más eficaces, que permitan mejorar el control de estas entidades, especialmente aquellas que habitualmente son más resistentes. En los últimos años, el uso de anticuerpos monoclonales contra antígenos específicos de poblaciones linfocitarias o contra moléculas proinflamatorias ha conocido una gran expansión, y se han revelado como una alternativa útil en las enfermedades autoinmunitarias.Se ha realizado una búsqueda intensiva en Medline usando como palabras clave: neuromuscular, miopatía, neuropatía, miastenia, Lambert-Eaton, anticuerpo monoclonal, rituximab, alemtuzumab, anti-TNF-α. Desarrollo: Los ensayos clínicos realizados para valorar la eficacia de los anticuerpos monoclonales en patología neuromuscular son muy escasos y de tamaño muy reducido, de modo que la experiencia en este ámbito se limita fundamentalmente a casos anecdóticos o series cortas de pacientes tratados de forma abierta. Los datos publicados son esperanzadores, habiéndose observado respuestas favorables en pacientes resistentes a tratamientos clásicos y en patologías que habitualmente no responden a los fármacos inmunosupresores habituales. Por otro lado, se ha observado que los anticuerpos anti-TNF-α pueden provocar la aparición de enfermedades neuromusculares autoinmunitarias. Conclusiones: Los anticuerpos monoclonales pueden ser una alternativa terapéutica eficaz en la patología neuromuscular autoinmune, pero es preciso confirmar las respuestas favorables observadas mediante ensayos clínicos controlados con un número suficiente de pacientes. Keywords: Autoimmune neuropathies, Guillain-Barre, Chronic demyelinating polyneuropathy, Multifocal motor polyneuritis, Anti-MAG neuropathy, Myasthenia, Lambert-Eaton, Polymyositis, Dermatomyositis, Inclusion body myositis, Monoclonal antibodies, Rituximab, Alemtuzumab, Palabras clave: Neuropatías autoinmunitaria, Guillain-Barré, Polineuropatía desmielinizante crónica, Multineuritis multifocal motora, Neuropatía anti-MAG, Miastenia, Lambert-Eaton, Polimiositis, Dermatomiositis, Miositis de cuerpos de inclusión, Anticuerpos monoclonales, Rituximab, Alemtuzumab